National Bobwhite Conservation Initiative Focus Area Monitoring in the 2C Focus Area, Missouri - Beth Emmerich; W. T. White; E. Lee Metcalf (National Quail Symposium Proceedings, 2017)
The Missouri Department of Conservation (MDC) began establishing Quail Focus Areas (QFAs) on private lands in 2004. The goal of QFAs is to increase and expand quail habitat management efforts at a larger scale. Because most (93%) of Missouri’s landscape is in private ownership, habitat improvement programs on private lands have greater potential to impact quail populations than on public lands alone. In spring of 2013, a group of MDC staff and Quail Forever biologists began monitoring bobwhite quail (Colinus virginianus) and songbirds in a portion of the 2C QFA in Carroll County, Missouri as well as in a control area (without habitat management for bobwhite). This effort is part of the Coordinated Implementation Plan developed by the National Bobwhite Technical Committee as a part of the National Bobwhite Conservation Initiative. The goal of the monitoring plan is to document within 5-10 years, if quail habitat management can achieve sustainable bobwhite populations. We selected a 5,200-acre (2014-ha) portion of the 2C QFA where habitat management for quail has been conducted through efforts by landowners, MDC staff and Quail Forever volunteers. Point transect surveys are conducted at 48 250-m radius points in the spring for bobwhite and other songbirds and at 12 500-m radius points in the fall for bobwhite coveys. In 2013, we heard three times more quail in the focus area, compared to the control area. We heard between 2 and 3 times more dickcissels (Spiza americana), eastern meadowlarks (Sturnella magna), and field sparrows (Spizella pusilla) in the focus area versus the control, demonstrating that habitat management for quail also benefits a variety of other grassland bird species. During the spring of 2014, we heard a total of 426 bobwhites in the focus area compared to only 78 in the control area. In fall 2013, we heard an average of 2.7 coveys per point in the focus area, and only 0.3 coveys per point in the control area. In fall 2014, we heard an average of 3.9 coveys per point inside the focus area and 1.8 coveys per point in the control area. Additional data from 2015 will be presented. These surveys continue to show that habitat management for bobwhite continues to benefit other grassland bird species.
Keywords: Colinus virginianus; northern bobwhite; point transect surveys; focus area; monitoring; private land; Missouri; nbci